Insights into Islamic Education Research: A Bibliometric Study to Analyzing Research Development Islamic Education - Jessika Ria Puspitasari; Istanto Istanto; Muhamad Subhi Apriantoro; Afief El Ashfahany (AL-FIKRA, 2023)
This study aims to determine the mapping of the development and direction of Islamic education research in publications indexed by the Scopus database. This study used bibliometric analysis techniques to explore all publications indexed in the Scopus database on Islamic education from 1974 to 2023. The data obtained were analyzed using Excel and R/R-Studio. VOSviewer is used to perform a visual analysis of keyword occurrence and document citations stimulant. The author found 593 publications that fit the subject, function, and criteria set. The results of this study show that publications on Islamic education were the most researched in 2020 with as many as 75 documents. The country that contributes the most publications is Indonesia. The highest affiliation is occupied by the International Islamic University Malaysia. The most relevant author is Nuryana, Z. The limitation of this study is only taking data sets or recording to publications that are Scopus in desks. Other national and international databases were not taken into account in the study. This study presents a brief overview of the literature that can be accessed by researchers working in education and provides recommendations for research.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersianÂ // Â TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//